Holocaust Memory and the Cold War (De Gruyter, 2024)
The Cold War influenced how people, societies and states dealt with the Holocaust and its aftereffects. This book challenges previous perceptions that the democratic West embraced commemoration while the totalitarian East did not. Its contributions show how political interests shaped commemoration on both sides of the Iron Curtain and how individual actors carved out space to remember the Holocaust beyond the dominant narratives.